Food Waste During A Global Pandemic: A qualitative study on food waste management in South Africa’s retail sector and the effects of Covid-19 - Lubala, Jonathan (The IIE, 2020)
Every year a third of the food produced globally is wasted. In South Africa, an estimated total of 10 million tons of wasted food adds to this statistic (World Wide Fund for Nature, 2017). This staggering amount depicts a grim reality for many South Africans, where poor food waste management has a sweeping impact across the country, further straining the disproportionate access to food. The embedded loss in resources such as water, energy, and labour used to produce food that is ultimately wasted, comes at a high cost to the South African environment and economy. South Africa’s retail sector plays a large role as a major contributor to food waste (20%) within the country (World Wide Fund for Nature, 2017). Although access to food is a Constitutional right, millions in both urban and rural areas continue to suffer daily from hunger and malnutrition - a reality that has been exasperated by the Covid-19 pandemic. As a leader in the food retail sector, Woolworths has made significant contributions to the reduction of food waste within its business, as well as consistent donations to local food waste initiatives. However, the lack of collective knowledge, reporting transparency and effective action within the food industry highlights the necessity for further local studies on food waste management, the effects of a crisis on food waste, and how improvements can be implemented. Farmers, food manufacturers, distributors, food retailers and households all regularly waste excess foods, which could be otherwise used and redistributed to help alleviate hunger within South Africa (World Wide Fund for Nature, 2018). Adopting a Critical Realist perspective, this study aims to use qualitative research methods and comparative analysis to propose recommendations vis-a-vis how Woolworths and the food sector as a whole can further improve its food waste management practices for the betterment of South Africa.
Keywords: Wasted food; Hunger; Malnutrition; Food waste initiatives; Woolworths; Retail industry; Food sector